Reoviruses: Entry, Assembly and Morphogenesis - SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Reoviridae family members are large, complex viruses that infect human, animals, plants and insects. They are unique in that they lack lipid envelopes and package their genomes of discrete double-stranded segments of RNA within multi-layered capsids. Lack of a lipid envelope has allowed three-dimensional structures of these large complex viruses to be obtained. The capsids of these viruses undergo cell entry, uncoating, the enzymatic functions necessary for transcription of the genome, and are later involved in egress from host cells. Recent years have seen an increase in our knowledge of the structure of these viruses coupled with substantial progress in unravelling the molecular details of these processes. Intriguingly, despite their diversity in hosts, structures and modes of transmission, striking parallels have emerged in the molecular interactions necessary for the essential processes of virus entry, assembly and release. This book reviews our current understanding of Reoviridae entry, disassembly/assembly and egress in addition to updating high resolution structures of viral proteins and capsids from three different genera of the family.
Attachment and Cell Entry of Mammalian Orthoreovirus -- Early Steps in Rotavirus Cell Entry -- Early Steps in Avian Reovirus Morphogenesis -- Bluetongue Virus Assembly and Morphogenesis -- Reovirus Structure and Morphogenesis -- Rotavirus Genome Replication and Morphogenesis: Role of the Viroplasm -- Rotavirus Proteins: Structure and Assembly -- Structural Studies on Orbivirus Proteins and Particles -- Rotavirus Assembly: An Alternative Model That Utilizes an Atypical Trafficking Pathway.
Keywords: Virology; Virology